TEKNIK PEMBENIHAN ABALONE (HALIOTIS SQUAMATA) DI BALAI PERIKANAN BUDIDAYA LAUT LOMBOK - SARI, WIDYA KARTIKA; AMINULLAH, AMINULLAH (Universitas Mahasaraswati K. Mataram, 2024)
The aim of this research is to describe the abalone (Haliotis squamata) hatchery technique at the Lombok Marine Aquaculture Center (BPBL). This research is participatory research, researchers took part in all activities at the Lombok Marine Aquaculture Center (BPBL). Data collection methods are by observation and documentation. The data obtained was analyzed using descriptive statistics. The data collected is related to abalone hatching techniques. The results of research regarding abalone hatchery techniques at the Lombok Marine Cultivation Fisheries Center went through several stages, namely container preparation, gonad maturity selection, stimulation, spawning, abalone stocking, feeding, water quality management and harvesting